2020
DOI: 10.1101/2020.10.19.345082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Filopodia-based contact stimulated collective migration drives tissue morphogenesis

Abstract: Cells migrate collectively to form tissues and organs during morphogenesis. Contact inhibition of locomotion (CIL) drives collective migration by inhibiting lamellipodial protrusions at cell-cell contacts and promoting polarization at the leading edge. Here, we report on a CIL-related collective cell behavior of myotubes that lack lamellipodial protrusions, but instead use filopodia to move as a cohesive cluster in a formin-dependent manner. Genetic, pharmacological and mechanical perturbation analyses reveal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 60 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…However, close examination of the migrating myotubes employing the newly established 4D imaging methods revealed that all myotubes resembled each other in terms of cell protrusion. [4] Unlike border cell migration, no subset of cells seemed to exclusively react to an outside gradient. Instead, myotubes likely self-regulate their behavior.…”
Section: Testis Myotube Collective Cell Migration-common and Unique Aspectsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, close examination of the migrating myotubes employing the newly established 4D imaging methods revealed that all myotubes resembled each other in terms of cell protrusion. [4] Unlike border cell migration, no subset of cells seemed to exclusively react to an outside gradient. Instead, myotubes likely self-regulate their behavior.…”
Section: Testis Myotube Collective Cell Migration-common and Unique Aspectsmentioning
confidence: 99%
“…[43][44][45] Recent observations in vitro and in vivo have further challenged our current view of the function of filopodia in migrating cells. [4,46] Adebowale and colleagues found that filopodial protrusions mediate migration of cultured human cancer cells on soft, fast-relaxing substrates suggesting that filopodia-based migration may play a key role in cancer metastasis in physiologically relevant 3D environments [46] (Figure 1A). Recent livecell-imaging experiments further showed that filopodia play not only an important role in cancer progression, but also in collective migration of testis nascent myotubes during Drosophila development (Figure 1D).…”
Section: Filopodia-based Cell Migrationmentioning
confidence: 99%
See 3 more Smart Citations